2023
DOI: 10.1186/s12951-023-01770-0
|View full text |Cite
|
Sign up to set email alerts
|

Orally administration of cerium oxide nanozyme for computed tomography imaging and anti-inflammatory/anti-fibrotic therapy of inflammatory bowel disease

Abstract: Background Inflammatory bowel disease (IBD) is a chronic nonspecific disease with unknown etiology. Currently, the anti-inflammatory therapeutic approaches have achieved a certain extent of effects in terms of inflammation alleviation. Still, the final pathological outcome of intestinal fibrosis has not been effectively improved yet. Results In this study, dextran-coated cerium oxide (D-CeO2) nanozyme with superoxide dismutase (SOD) and catalase (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 63 publications
0
27
0
1
Order By: Relevance
“…144 Furthermore, a dextran-coated cerium oxide (D-CeO 2 ) nanozyme with superoxide dismutase and catalase activities was demonstrated to exhibit ROS scavenging activity and suppress pro-inflammatory cytokines to protect cells from H 2 O 2 -induced oxidative stress. 145 In addition to this, a Cu-only superoxide dismutase (SOD5)-based single atom nanozyme (Cu-SAzyme) dramatically decreased various organ damage and death in activated inflammatory cells by eliminating excess ROS and pro-inflammatory cytokines. 146 Therefore, it can be concluded that nanozymes can serve as potential ROS scavengers and cytokine modulators to induce the antiinflammatory response.…”
Section: ■ Nanozymes As Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…144 Furthermore, a dextran-coated cerium oxide (D-CeO 2 ) nanozyme with superoxide dismutase and catalase activities was demonstrated to exhibit ROS scavenging activity and suppress pro-inflammatory cytokines to protect cells from H 2 O 2 -induced oxidative stress. 145 In addition to this, a Cu-only superoxide dismutase (SOD5)-based single atom nanozyme (Cu-SAzyme) dramatically decreased various organ damage and death in activated inflammatory cells by eliminating excess ROS and pro-inflammatory cytokines. 146 Therefore, it can be concluded that nanozymes can serve as potential ROS scavengers and cytokine modulators to induce the antiinflammatory response.…”
Section: ■ Nanozymes As Biosensorsmentioning
confidence: 99%
“…Moreover, the Prussian blue (PB) nanozyme was investigated as a novel compound for repairing cutaneous wounds via the reduction of excessive ROS and inflammatory regulation . Furthermore, a dextran-coated cerium oxide (D-CeO 2 ) nanozyme with superoxide dismutase and catalase activities was demonstrated to exhibit ROS scavenging activity and suppress pro-inflammatory cytokines to protect cells from H 2 O 2 -induced oxidative stress . In addition to this, a Cu-only superoxide dismutase (SOD5)-based single atom nanozyme (Cu-SAzyme) dramatically decreased various organ damage and death in activated inflammatory cells by eliminating excess ROS and pro-inflammatory cytokines .…”
Section: Nanozymes-based Disease Therapymentioning
confidence: 99%
“…Cao et al developed a dextran‐coated cerium oxide (D‐CeO 2 ) nanozyme by chemical precipitation which has potent ROS scavenging abilities to alleviate intestinal fibrosis. The D‐CeO 2 nanozyme efficiently scavenged ROS and regulated the fibrosis‐related microenvironment in TNBS‐ and DSS‐induced intestinal fibrosis mice models, providing a practical use for nanozymes with ROS scavenging capabilities in anti‐fibrotic strategies 63 …”
Section: Intestinal Fibrosismentioning
confidence: 99%
“…Evidence indicates that ROS activates and promotes TGF-β signaling, in turn, TGF-β1 boosts ROS production and decreases its elimination, which promotes fibrogenesis. 62 63…”
Section: Tissue Levelmentioning
confidence: 99%
“…Hence, ALG is a promising material for colon targeting. [17,18] Therefore, we hypothesized that ALG-coated Man-biotin dual-modified polymer microspheres might be an intelligent oral targeted delivery system for UC. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%